PENGARUH DOPING AL TERHADAP BAND GAP ENERGY LAPISAN TIPIS ZNO - Listiorini Listiorini; Helga Dwi Fahyuan; Ngatijo Ngatijo (Prodi Fisika FST UNJA, 2018)
[Title: The Effect of dopping Al on the Value of Band Gap Energy Thin Film of ZnO] A research has been conducted on the effect of doping Al on the value of band gap energy thin film ZnO with variation of concentration Al 0%, 4%, 6%, 8% and 10%. A thin film ZnO/Al is grown on a glass substrate using a spin coating technique. The resulting thin film was characterized using a UV-Vis measure the ZnO/Al transmittance value in the wavelength range 200-700 nm. Then calculate the value of band gap energy using the Swanepoel and touc Plot and obtained value band gap energy at concentration 0%, 4%, 6%, 8% and 10% successive is 3,94 eV, 3,25 eV, 3,24 eV, 3,22 eV dan 3,84 eV. Of the results obtained, the smallest band gap energy value at ZnO/Al 8% concentration of 3,22 eV. Keyword: Thin Film, Dopping, Band Gap Energy